Research methods in social relations - Hoyle, Rick H. 4 0 16; Harris, Monica J.,;Judd, Charles M.; 5 (Australia : Wadsworth/ Thomson Learning, 2002)
An introduction to social science research methods that provides information on the latest trends and developments in social science research and their implications.
Includes bibliographical references and indexes.
Professional.;Adult.
Keywords: 2 -- 0; 6; Research;Methodology.;Research;Methodology. -- Social sciences;Social sciences; 20; 2